Microbiology of the food chain. Horizontal method for detection and enumeration of Campylobacter spp. Colony-count technique. Inclusion of methods for molecular confirmation and identification of thermotolerant Campylobacter spp and changes in the performance testing of culture media Part 2, (23rd February 2023) - British Standards Institution,
No abstract available